Kronik Gerakan Serikat Buruh di Indonesia: Peta dan Sejarah - Ahmad, Iqbal Faza; Al Ayubbi, Syaefuddin Ahrom (Sahabat Akademia Group, 2024)
This research focuses on studying the dynamics of the trade union movement in Indonesia in a historical review and current map of the Trade Union Confederation/Labor Unions registered with the Ministry of Manpower. This study is a qualitative combination of literature and empirical research, combining literature and field data to explore the dynamics of trade unions in Indonesia, especially confederations. Since the 19th century, the birth of the Dutch East Indies Teachers' Workers' Union in 1879 began the emergence of the Workers' Union Movement (SP) or Labor Unions (SB) in Indonesia. These labor organizations, especially in the transportation and plantation sectors, played a central role in Indonesia's struggle for independence. Over time, various labor organizations emerged that played a key role in national political dynamics, such as VSTP, PPKB, and the Indian Vakbonden Association (PVH). Despite experiencing challenges during the Japanese occupation and the failure of the PKI's political action in 1926, the labor movement continued to develop until post-independence, with a major role played by organizations such as SOBSI in the Old Order era, SPSI in the New Order era, and various organizations that emerged during the Reformation era. Since the Reformation era, new trade unions have emerged and old unions have emerged, driven by political reform and the rapid growth of trade and labor unions. The latest mapping shows that more than 4 million workers/laborers are members of more than 20 organizations under various federations and confederations. Organizations such as KSPSI AGN, KSPSI JUMHUR, KSPI, and KSPSI YRS have the most members.